ASSESSMENT RATING OF FE, CU AND ZN IN WATER AND IN TISSUES OF LUCIOBARBUS CALLENSIS (VALENCIENNES, 1842) AND CYPRINUS CARPIO CARPIO (LINNAEUS, 1785) AT K'SOB RESERVOIR (M'SILA - ALGERIA) - Mimeche, Fateh; Nouidjem, Yassine; Boudiaf, Leila; Medjenah, Nardjis; Mimeche, Hayet; Djamai, Soumia; Alouani, Radhouane (LIFE: International Journal of Health and Life-Sciences, 2018)
The aim of this study was to determine Fe, Cu and Zn in K’sob reservoir water (Msila - Algeria) and to estimate their concentration in the tissues of Cyprinus carpio carpio and Luciobarbus callensis, as an indicator of the quality of this aquatic ecosystem. The choice of these species is mainly based on endemism criteria; the Carp fish is representative species of the invasive fish communities but the Barbel is an endemic species inhabiting the course of a Wadi and the K’sob reservoir. Our study conducted from January to May 2014 with a monthly monitoring in order to analysis the concentration of the heavy metals in water and fish tissues. The reservoir water show different values of heavy metals between high concentration of Cu and a medium for Fe and Zn. While the higher concentrations of Copper were obtained from carp and important values of Iron and Zinc are shown in both species. These values appear compatible with our fish’s habitat and its diet.